Dibenzobarrelene-based azaacenes: emitters in organic light-emitting diodes - Ganschow, Michael; Koser, Silke; Hahn, Sebastian; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (Chemistry - a European journal, 2017)
The synthesis of soluble dibenzobarrelene-substituted azaacenes either by condensation reactions in solution or, more effectively, in the solid state by using a ball mill is reported herein. We relate their optical properties in thin films to their packing in the solid state. The targets are characterized by cyclic voltammetry, X-ray crystallography and UV/Vis and fluorescence analysis. Three highly fluorescent, amorphous azaacenes were processed into organic light-emitting diodes, and their improved performance (luminance, efficiency and efficacy) was compared with that of structurally related iptycene-based azaacenes.
First published: 26 January 2017
Gesehen am 15.06.2018